Organ-specific gene modulation: Principles and applications in cancer research. (28th February 2017) - Economopoulou, Panagiota; Psyrri, Amanda
Highlights: Gene modulators modify the activity of transcription factors. Gene modulators are overexpressed in a variety of cancers. Therapeutic gene modulation refers to the alteration of gene expression. Abstract: Microarray and next generation sequencing has led to the exploration of correlated gene patterns and their shared functions. Gene modulators are proteins that alter the activity of transcription factors and influence the expression of their target genes. It is assumed that modulators are dependent on transcription factors. Several algorithms have been developed for the detection of gene modulators. On the other hand, it is becoming increasingly evident that modulators play a crucial role in carcinogenesis by interfering with fundamental biologic processes. Therapeutic gene modulation that is based on artificial modification of endogenous gene functions by designer molecules is an exciting new field of investigation.